Quantitative analysis of soil dipterans in a beech ecosystem in „Mavrovo“ National Park, compared to oak ecosystems in Macedonia - Prelik, Dana (Macedonian Journal of Ecology and Environment, 2003)
In this paper, the results obtained from the quantitative analysis of dipterans in the beech ecosystem Calamintho grandiflorae-Fagetum in the National Prak „Mavrovo“ compared to oak ecosystems (Quercetum frainetto-cerris macedonicum) in both Galichica Mt. and surroundings of Veles are presented. The average numbers, seasonal dynamics and vertical distribution of the dipterans in the investigated ecosystems were studied.